Perception of discharge planning and quality of life among patients with coronary artery diseases / Iffah Jamaludin and Syarifah Nursyazwani Syed Omar - Jamaludin, Iffah; Syed Omar, Syarifah Nursyazwani (2019)
Background: Discharge planning is an essential component for a transition of care across health settings and providers. Quality of life (QoL) is defined as an individual's unique cognition and a way to express feelings about a person's health status affected by the physical, mental, emotional and social status of a person. The impact of a coronary event risked a person's life and may cause disability, thus the rise of attention for proper discharge planning and QoL among coronary artery diseases (CAD) patients. Objective: To identify the level of perception of discharge planning and quality of life among patients with CAD. Method: This is a cross-sectional study design using questionnaires. A Patient Continuity of Care Questionnaire (PCCQ), which is an index of a 25-item used to assess the perception of discharge planning. A MacNew QoL questionnaire, comprised of a 27-item used to assess the health-related QoL. The questionnaires were distributed to 152 patients in UiTM Medical Specialist Centre over two months. The correlation between PCCQ score and QoL were examined using Spearman Ranks correlation analysis. Result: The result of this study showed among 152 patients participated in the survey, n=152 (100%) had a high perception of discharge planning. Level of QoL which were classified into 3 subscales (emotional, physical and social), most of the respondents achieve higher QoL in emotional aspects (n=152, 100%) and low QoL in physical (n=124, 81.6%) and social (n=92, 60.5%) aspects. There is no correlation observed between the level of perception of discharge planning and the level of QoL. The results are significant when p<0.05 for the relationship between the level of perception of discharge planning with age groups (p=0.002), gender (p=0.018), level of education (p=0.135), marital status (p=0.814) and family history of heart disease (p=0.449). The findings of p<0.05 is achieved for the relationship between the level of QoL with age groups, QoL (physical and social) with marital status, QoL (emotional and social) with a family history of heart disease, whereas p>0.05 for gender and level of education. Conclusion: In conclusion, the respondents had a high level of perception of discharge planning, high emotional QoL but low physical and social QoL. Future research should identify the factor that can influence the perception of discharge planning and QoL, to determine the importance of both variables, especially in patients with CAD.